Antimicrobial peptide GH12 as root canal irrigant inhibits biofilm and virulence of Enterococcus faecalis. (14th April 2020) - Li, Y.; Wang, Y.; Chen, X.; Jiang, W.; Jiang, X.; Zeng, Y.; Li, X.; Feng, Z.; Luo, J.; Zhang, L.
Abstract: Aim: The objectives of this laboratory‐based study were to investigate the effects of GH12 on Enterococcus faecalis biofilm and virulence. Methodology: Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of GH12 against E. faecalis were first determined. A time‐kill assay was further conducted. The effects of GH12 on the expression of virulence and stress genes in E. faecalis were evaluated by RT‐qPCR. Crystal violet stain was used to investigate the effects of GH12 on E. faecalis biofilm formation and 1‐day‐old biofilm . Finally, an ex vivo tooth model contaminated with E. faecalis was used to evaluate the antimicrobial activity of GH12 as an irrigant by CFU counting, SEM and CLSM. One‐way anova and Tukey's multiple comparisons test were used to compare the differences amongst groups (α = 0.05). Results: The MICs and MBCs of GH12 against E. faecalis were 8.0 ± 0.0 and 16.0 ± 0.0 mg L −1, respectively, and GH12 at 32.0 mg L −1 reduced the bacterial numbers by more than 99.9% within 1 min. Various virulence genes ( efaA, esp and gelE ) and stress genes ( dnaK, groEL, ctsR and clpPBCEX ) in E. faecalis were significantly downregulated by GH12 at sub‐MIC levels ( P < 0.05) . Additionally, both E. faecalis biofilm formation and the biomass of 1‐day‐old E. faecalis biofilm were significantly reduced by GH12 ( P < 0.05). Elimination of E. faecalis in biofilms from root canal walls was achieved through irrigation with 64.0 mg L −1 GH12 for 30 min. CLSM analysis revealed that GH12 at 64.0 mg L −1 was most effective in eliminating bacteria within dentinal tubules ( P < 0.05). Conclusion: In a laboratory setting, and when used as an irrigant, GH12 suppressed E. faecalis, downregulated specific virulence and stress‐associated genes, eliminated intracanal E. faecalis protected by biofilms and killed bacteria in dentinal tubules. These results emphasize the need for preclinical and clinical studies to explore the potential of GH12 as an antimicrobial agent during root canal treatment.